The role of spatial perception in auditory looming bias: neurobehavioral evidence from impossible ears - Greif, Tobias; Barumerli, Roberto; Ignatiadis, Karolina; Tóth, Brigitta; Baumgartner, Robert (Frontiers in Neuroscience, 2025)
IntroductionSpatial hearing enables both voluntary localization of sound sources and automatic monitoring of the surroundings. The auditory looming bias (ALB), characterized by the prioritized processing of approaching (looming) sounds over receding ones, is thought to serve as an early hazard detection mechanism. The bias could theoretically reflect an adaptation to the low-level acoustic properties of approaching sounds, or alternatively necessitate the sound to be localizable in space.MethodsTo investigate whether ALB reflects spatial perceptual decisions or mere acoustic changes, we simulated ears that disrupted spectrospatial associations on the perceptual level while maintaining the original spectrospatial entropy on the acoustic level. We then assessed sound localization, ALB and distance ratings.ResultsCompared to native ears, these novel ears impaired sound localization in both the direction and ego-centric distance dimensions. ALB manifestation also differed significantly between native and novel ears, as evidenced by behavioral discrimination performance and early cortical activity (N1 latency). Notably, the N1 electroencephalographic response closely resembled distance ratings, suggesting a strong link between spatial perception and ALB-related neural processing. Integrating this neural marker into a hierarchical perceptual decision-making model improved explanatory power, underscoring its behavioral relevance.DiscussionThese findings suggest a strong link between the localizability of sounds and their ability to elicit ALB.